The Effectiveness of Giving Moringa Oleifera Formulation to Increase Hemoglobin Levels in Pregnant Women - Usman Usman; Fitriani Umar; Ruslang T (Sarana Ilmu Indonesia (salnesia), 2022)
Pregnancy accompanied by anemia was still a public health problem in Indonesia in recent years. This study aimed to determine the effectiveness of the formulation of Moringa oleifera on increasing hemoglobin levels in pregnant women. This type of research was quasy experimental with the One-Group Pre-Post test approach. The study was conducted for 6 months in Parepare City with a total sample of 33 pregnant women. Data was collected by measuring hemoglobin levels 2 times and filling out a questionnaire. Data analysis used paired sample t-test. The results showed that 33 subjects had hemoglobin levels of 10,86 mg/dl before treatment and after being given the formulation, the subjects' hemoglobin levels were 12,25 mg/dl with p value = 0,002. Based on the results of the study, it can be concluded that the administration of Moringa leaf formulation is effective in preventing the incidence of anemia in pregnant women.